Desayuno saludable en el rendimiento académico de los niños de nivel inicial II de la Unidad Educativa Fe y Alegría. ciudad de Riobamba - Tenesaca Shigla, Jennifer Daniela (2025)
The main objective of this research project, entitled “Desayuno saludable en el rendimiento académico de los niños de nivel inicial II de la Unidad Educativa Fe y Alegría, en la ciudad de Riobamba” was to determine the influence of a healthy breakfast on the academic performance of 5-year-old children attending that institution. The methodology applied was developed using a quantitative approach, with a descriptive, non-experimental, cross-sectional design. The study population consisted of 20 parents and one teacher from sublevel II. A survey was used as the data collection technique, which allowed for the collection of relevant data on the children's eating habits before attending classes. The results showed that, although most children eat some type of breakfast, it does not always meet the criteria for a complete and balanced diet. Likewise, it was identified that children who do not eat breakfast adequately show signs of drowsiness, irritability, and lower school performance, as reported by the teacher. Based on these findings, a weekly menu proposal was developed with healthy, nutritious, inexpensive, and easy-to-prepare breakfasts, using local foods such as potatoes, corn, beans, and mellocos. This proposal was presented in an educational brochure aimed at parents, with the purpose of promoting healthy eating habits at home and, in this way, contributing to the improvement of children's academic performance.